Long-term patterns of abiotic drivers of mosquito activity within summer ranges of Northern Alaska caribou herds (1979–2009) - Archana Bali; Vladimir A. Alexeev; Robert G. White; Don E. Russell; A. David McGuire; Gary P. Kofinas (Rangifer, 2013)
-